2011
DOI: 10.5539/ijef.v3n4p162
|View full text |Cite
|
Sign up to set email alerts
|

Projecting the Possible Impacts of the National Economic Empowerment and Development Strategy (NEEDS) on Human Development in Nigeria

Abstract: The study investigated the possible impact of National Economic Empowerment and Development Strategy (NEEDS) on human development in Nigeria. NEEDS is a home-groomed economic and social package focused on fighting poverty and enthroning a people-centered developmental programmes. The paper evaluates each of the major thrusts of NEEDS by highlighting their respective demands for new patterns of human development. Also, collaborative and interactive model of human development is presented. The paper highlights t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…NEEDS phase II commenced in June, 2007 with the expectation of spearheading Nigeria's industrialization. Akintunde and Ojiabor (2006) in Ogundele, et al (2011) reported that the implementation of NEEDS Phase II would build on the achievements of NEEDS Phase I, which started in 2004. Under NEEDS Phase II, it was stated that there would be a focus on employment generation and aggressive public infrastructural development.…”
Section: Discussionmentioning
confidence: 99%
“…NEEDS phase II commenced in June, 2007 with the expectation of spearheading Nigeria's industrialization. Akintunde and Ojiabor (2006) in Ogundele, et al (2011) reported that the implementation of NEEDS Phase II would build on the achievements of NEEDS Phase I, which started in 2004. Under NEEDS Phase II, it was stated that there would be a focus on employment generation and aggressive public infrastructural development.…”
Section: Discussionmentioning
confidence: 99%
“…Other reviewers of the policy highlighted the need for new patterns of human development for the programme to succeed (Ogundele, Hassan, & Abdul-Azeez, 2011). With respect to the contribution of NEEDS to the development of infrastructural facilities, Olusoji and Oloba (2014) indicate that the policy had not been able to eliminate generation deficits, expand transmission and distribution networks, and increase rural access to electricity, which are the necessary requirements for economic growth and poverty reduction through the provision of employment.…”
Section: Poverty Reduction Policies In Nigeria: the National Economicmentioning
confidence: 99%
“…Nigeria had produced some of National Development plans, which represented the objectives and aspirations of the nation, in charting its course of monetary, social and political development. 1975-1980, Fourth National Development Plan 1981-1984, the 5th National Development plan of 1989 and the three every year rolling plans because the imaginative and prescient 1990s which culminated within side the imaginative and prescient 2010 for Nigeria (Ogundele and Opeifa, 2004) [12] . In the First and Second National Development Plans, the standards used have been: (i) that specialize in funding with best increase potentials (ii) making sure the feasibility of numerous authorities proposals (iii) Emphasizing monetary desirability of projects, and (iv) making sure the fulfilment of most increase rate.…”
Section: Introductionmentioning
confidence: 99%